Understanding the Early Stage of Planet Formation: Design and Demonstration of the Space Experimental Apparatus - Chenyang Huang; Yang Yu; Zhijun Song; Bin Cheng; Wenyue Dai (Aerospace, 2023)
Planet formation begins with the collision and growth of dust in protoplanetary disks. Concerning the basic cognition of the early stage of planet formation, a long-standing weakness of the research is a comprehensive physical model describing the collisional evolution of dust particles. Microgravity experiments providing original data are crucial in developing related theories. In this work, we propose an experimental scheme for observing the collisional growth of dust analogues under a unidirectional and continuous shearing process, aiming at a future implementation in space experiments. The experimental process is simulated using the discrete element method, and the atlas of the design parameter versus the evolutionary path is depicted. We notice fractal structures and growth stalling as remarkable outcomes in the process of collisional growth, which is analogous to the evolutionary mechanism in the ancient protoplanetary disks. Based on these phenomena, we determine the sensitive design parameters, i.e., the shear velocity and the filling factor, which serve as the recommended parameters in future space experiments. The validation using numerical experiments shows that the experimental scheme with proper design parameters is feasible, which promises to generate constructive data that will facilitate the development of planet formation theory.